2023
DOI: 10.3389/fpsyg.2023.1098916
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the relationships between emotions and achievement of EFL learners in China: Engagement as a mediator

Abstract: Emotions are attracting growing attention in second language acquisition (SLA), especially with the advent of positive psychology (PP). The fundamental role of emotions in affecting learners’ second language (L2) achievement has been well-documented. Evidence also indicates that emotions can significantly influence learners’ L2 learning engagement which profoundly impacts their academic performance. However, the links between emotions, engagement, and L2 achievement remain underexplored. To contribute to this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 95 publications
3
9
0
Order By: Relevance
“…Moreover, the correlation between academic emotions and language performance is influenced by different language domains, with FLE being an exception. Specifically, speaking activities are found to have the most profound impact on FLE, while reading performance is significantly influenced by FLB (Wang et al, 2023).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Moreover, the correlation between academic emotions and language performance is influenced by different language domains, with FLE being an exception. Specifically, speaking activities are found to have the most profound impact on FLE, while reading performance is significantly influenced by FLB (Wang et al, 2023).…”
Section: Discussionmentioning
confidence: 94%
“…FLE and FLA tend to have a negative correlation, indicating that when learners enjoy the journey of acquiring language skills, they tend to experience less anxiety (Chen et al, 2023;Tsang & Dewaele, 2023). On the other hand, FLE is negatively associated with FLB (J. M. Tsang & Dewaele, 2023; Wang et al, 2023), whereas there is a positive correlation between FLA and FLB (Zhao & Wang, 2023). However, the relationship between FLA, FLE, and FLB is not static but complex and dynamic, varying according to the nature of the learning tasks (Bielak, 2022;Wang et al, 2023).…”
Section: Literature Review 21 Fle Fla and Flbmentioning
confidence: 99%
See 2 more Smart Citations
“…This highlights the significance of nurturing positive parent-child relationships, particularly ones that are characterized by emotional warmth and reduced feelings of rejection. This can help improve children's mathematical self-confidence and reduce related anxiety [9]. A further investigation revealed that the presence of depressive symptoms had the ability to forecast levels of academic and emotional selfefficacy, with no discernible variance based on gender, after a period of six months [10].…”
Section: Correlation Between Self-efficacy and Depression And Anxietymentioning
confidence: 96%